2020
DOI: 10.1007/s00170-020-06413-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the surface quality and stress corrosion cracking resistance of AISI 316L stainless steel via precision end-milling operation

Abstract: This study presents a two-fold investigation on precision end-milling of stainless steel (AISI 316L). First, the impact of end-milling variables (cutting speed and feed rate) on the surface quality (surface roughness, microhardness, and surface morphology) was analyzed. The best surface quality with surface roughness (Ra) 0.65 ± 0.02 μm was observed for cutting speed of 140 m/min and 0.025 mm/tooth of feed rate. Microhardness was increased with increment in cutting speed. Second, the impact of surface roughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Hence to accomplish the desired features and productivity, the experimental run 23 trailed by the run of 22 and 24 (exclusion of 5 mm min −1 cutting feed) and the predicted optimal machining conditions and cutter nomenclature are as follows: Under Negative RRA cutter, the cutting feed and speed of 15 mm min −1 and 28.26 m min −1 to achieve lowermost cutting force requirement and surface roughness followed by the cutting feed and speed of 15 mm min −1 and 14.13 m min −1 under similar RRA cutter. From the above interpretation, it is confirmed that the Negative RRA cutter has invoke better observable features and productivity [20][21][22][23][24][25]. 3.6.…”
Section: Taguchi S/n Ratio Analysis On the Observable Characteristics...mentioning
confidence: 84%
“…Hence to accomplish the desired features and productivity, the experimental run 23 trailed by the run of 22 and 24 (exclusion of 5 mm min −1 cutting feed) and the predicted optimal machining conditions and cutter nomenclature are as follows: Under Negative RRA cutter, the cutting feed and speed of 15 mm min −1 and 28.26 m min −1 to achieve lowermost cutting force requirement and surface roughness followed by the cutting feed and speed of 15 mm min −1 and 14.13 m min −1 under similar RRA cutter. From the above interpretation, it is confirmed that the Negative RRA cutter has invoke better observable features and productivity [20][21][22][23][24][25]. 3.6.…”
Section: Taguchi S/n Ratio Analysis On the Observable Characteristics...mentioning
confidence: 84%
“…For example, the variation of microhardness of stainless steel 316L processed in AM, SM and HM techniques is displayed in Figure 22 . Subtractive processes, such as milling, provide higher value of microhardness due to the high temperature generated at chip-tool interfaces [ 203 ]. Higher microhardness observed in the parts produced by EDM process due to the deposition of hard thin re-cast layer on the workpiece surface [ 204 ].…”
Section: Critical Analysis and Challenges In Intelligent Manufacturingmentioning
confidence: 99%
“…Austenitic stainless steel is a common material that has good corrosion resistance, excellent mechanical strength, low thermal expansion, lower process costs, and good reliability [1]. Most manufacturing industries use this material as the primary material for making their products.…”
Section: Introductionmentioning
confidence: 99%